Physical activity and physical function in older adults: the 45 and up study - Yorston, Lisa C.; Kolt, Gregory S.; Rosenkranz, Richard R. (My University, 2012)
OBJECTIVES: To determine the strength of the relationship between physical activity and physical function in older adults. DESIGN: Cross-sectional. SETTING: The 45 and Up Study baseline questionnaire, New South Wales, Australia. PARTICIPANTS: Ninety-one thousand three hundred seventy-five Australian men and women aged 65 and older from the 45 and Up Study. MEASUREMENTS: Physical activity engagement (Active Australia Survey), physical function (Medical Outcomes Study Physical Functioning), psychological distress (Kessler- 10), and self-reported age, smoking history, education, height, and weight were all measured. RESULTS: Higher levels of physical activity were associated with better physical function in older adults (correlation coefficient = 0.166, P < .001). Participants engaging in higher levels of physical activity had progressively lower likelihoods of functional limitation (middle tertile: odds ratio (OR) = 0.39, 95% confidence interval (CI) = 0.38– 0.41; highest tertile: OR = 0.28, 95% CI = 0.27–0.29). This relationship remained significant, but weakened slightly, when adjusted for age, sex, body mass index, smoking history, psychological distress, and educational attainment (middle tertile: adjusted OR (AOR) = 0.48, 95% CI = 0.46–0.50; highest tertile: AOR = 0.36, 95% CI = 0.34–0.37). CONCLUSION: There is a significant, positive relationship between physical activity and physical function in older adults, with older adults who are more physically active being less likely to experience functional limitation than their more-sedentary counterparts. Level of engagement in physical activity is an important predictor of physical function in older adults.
Keywords: Older adults; Psychological distress; Sedentary lifestyle; Activities of daily living; Aging